Juvenile granulosa cell tumour: a rare clinical entity - Reddy, Kaliki Hymavathi; D, Pavithra; R, Ragini; S, Pallavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ovarian cancer is the third most common neoplasm of the female genital tract. Based on the cell type of origin, primary ovarian malignancies are classified into surface epithelium, germ cell, and sex cord tumors. Sex cord tumors account for 1% to 2% of ovarian malignancies. They may contain granulosa cells, theca cells, sertoli cells, or fibroblasts of gonadal stromal origin. Granulosa Cell Tumours (GCTs) account for approximately 2-5% of all ovarian tumors and can be divided into adult (95%) and juvenile (5%) types based on histologic findings. GCTs secrete estrogen thus resulting in menstrual irregularities in the affected individual. More serious estrogen effects can occur in various end organs such as uterus resulting in endometrial hyperplasia, endometrial adenocarcinomas and increased risk of breast cancers. Androgen production is also reported but rare and produces virilization in the affected women. Juvenile Granulosa Cell Tumours (JGCTs) are clinically & histopathologically distinct from the GCTs. They are rarely encountered but mostly in youngsters. Surgery is the primary modality of treatment with chemotherapy being reserved for advanced or recurrent disease states. We herewith report an interesting case of JGCT in a young teenage girl.